The role of a relative age effect in the first winter Youth Olympic Games in 2012 - Raschner, C.; Müller, L.; Hildebrandt, C. (British Journal of Sports Medicine, 2012)
Background - Owing to the separation into age groups at the first winter Youth Olympic Games (YOG), athletes differed in age by up to two years, leading to a potential relative age effect (RAE). Objective - The purpose of this study was to define the role of the RAE in the first winter YOG with regard to sex, type of sport and performance. Methods - The birth dates and anthropometric data of all 1021 athletes (557 male, 464 female, 14-19 years old) participating in 15 sports were analysed. A Chi² test was used to assess the difference between the observed and expected birth distributions. ANOVA (analysis of variance) and Kruskal-Wallis analyses were used to investigate differences in anthropometrics. Results - The birth date distribution of the overall sample was significantly different from an equal distribution, with an over-representation of athletes born shortly after the cut-off date (Chi²=284.7, p<0.001). A significant RAE was found in both male (Chi²=245.1, p<0.001) and female competitors (Chi²=74.6, p<0.001). An analysis based on the type of sport showed an RAE in all categories (strength—Chi²=229.9, p<0.001, endurance—Chi²=60.4, p<0.001 and technique-related sports Chi²=25.2, p=0.001). Relatively older competitors were also over-represented among medal winners (Chi²=47.9, p<0.001). Relatively older male competitors were significantly taller (p=0.005) and heavier (p<0.001) than younger competitors. No differences were found in female competitors. Conclusions - The results suggest that relative age had a highly significant influence on participation in various sports regardless of sex. A possible strategy to reduce the RAE would be a fixed quota for each birth year within the two-year age group across events.